Metal-clad laminate and its manufacturing method
Patent Information
- Application Number
- JP2020213775
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2040-12-23
AI Technical Summary
【0021】 本発明の金属張積層板は、金属層と絶縁樹脂層とが実用上十分な機械的強度を有し、金属層との接着性も良好であり、かつ、優れた熱伝導性を有するものである。また、マトリックス樹脂として熱可塑性ポリイミドを用いることによって金属層との接着性を担保しながら、熱伝導性フィラーの配合によって熱膨張係数を金属層の熱膨張係数に近づけることが可能となるため、反りが小さく、量産時や加工時のハンドリング特性にも優れている。従って、本発明の金属張積層板は、高い放熱性が求められるフレキシブル回路基板、電子機器、照明機器などの基板材料として工業的に広く用いることができる。
Smart Images

Figure 0007621112000008 
Figure 0007621112000009 
Figure 0007621112000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal-clad laminate having an insulating resin layer with excellent thermal conductivity and suitable for use in heat dissipation boards and circuit boards, and a method for producing the same. [Background technology]
[0002] In recent years, there has been an increasing demand for smaller and lighter electronic devices, such as mobile phones and smartphones, and flexible circuit boards, which are advantageous in reducing the size and weight of devices, have been widely used in the electronic technology field. In addition, the miniaturization of electronic devices has led to an increase in the degree of integration of circuits, and coupled with the increase in the speed of information processing, means for dissipating heat generated within the devices have attracted attention. In order to provide flexible circuit boards that are easy to process and have excellent heat dissipation properties, studies have been conducted to improve the thermal conductivity in the thickness direction by blending a thermally conductive filler into the polyimide that constitutes the insulating resin layer (for example, Patent Documents 1 and 2).
[0003] However, when a large amount of thermally conductive filler is mixed into the insulating resin layer to improve the heat dissipation efficiency, some of the thermally conductive filler protrudes from the surface of the insulating resin layer, causing poor appearance and surface smoothness, and poor adhesion with the metal layer. It is also known that the incorporation of a large amount of thermally conductive filler leads to a decrease in the mechanical strength of the insulating resin layer, such as the tear propagation resistance. In particular, when the insulating resin layer has a small thickness, the incorporation of the thermally conductive filler leads to embrittlement of the insulating resin layer, causing serious problems such as tearing and poor adhesion.
[0004] The metal-clad laminate of Patent Document 1 has an insulating resin layer that is 60 μm thick or more, while the metal-clad laminate of Patent Document 2 has an insulating resin layer that is about 25 μm thick, so the above problem is relatively unlikely to occur even if a large amount of thermally conductive filler is blended in. However, in the future, with further progress in miniaturization of wiring and higher standards required for heat dissipation efficiency, it is thought that it will become necessary to thin the insulating resin layer that contains the thermally conductive filler to, for example, 20 μm or less.
[0005] Patent Document 3 proposes that by blending α-alumina single crystal particles with an average particle size in the range of 0.3 μm to 1.5 μm inclusive with an insulating film having a thickness of 20 μm and a matrix resin of polyimide, and by further laminating an adhesive film on this insulating film, it is possible to improve the properties with a metal layer laminated thereon. However, since the adhesive film in Patent Document 3 is composed of a resin type different from the matrix resin of the insulating film, there is a concern that the thermal conduction path is likely to be interrupted at the interface between the insulating film and the adhesive film, which may lead to a decrease in heat dissipation efficiency, and there is also a problem that peeling is likely to occur at the interface. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-177929 A [Patent Document 2] JP 2012-213899 A [Patent Document 3] JP 2019-140094 A Summary of the Invention [Problem to be solved by the invention]
[0007] As described above, it has been desired to provide a metal-clad laminate in which the insulating resin layer in the metal-clad laminate is thinner than conventional ones, yet the insulating resin layer has sufficient mechanical strength for practical use, has good adhesion to the metal layer, and has excellent thermal conductivity.
[0008] Therefore, an object of the present invention is to provide a metal-clad laminate having an insulating resin layer which is thin, has excellent thermal conductivity, and has sufficient strength and adhesiveness for practical use. [Means for solving the problem]
[0009] As a result of extensive investigations into solving the above-mentioned problems, the inventors discovered that the above-mentioned problems could be solved by using a thermoplastic polyimide having a specific structure with excellent thermal conductivity as the matrix resin of the insulating resin layer in which a thermally conductive filler is blended in a metal-clad laminate, and by devising a method for forming the insulating resin layer, and thus completed the present invention.
[0010] That is, the metal-clad laminate of the present invention is a metal-clad laminate comprising a metal layer and an insulating resin layer containing a thermally conductive filler laminated on the metal layer. In the metal-clad laminate of the present invention, the thermally conductive filler has a volume average particle diameter of 2 μm or more and 5 μm or less, and the insulating resin layer has a thickness in the range of 5 μm or more and less than 20 μm. In addition, the metal-clad laminate of the present invention has a thermoplastic polyimide matrix resin containing a constitutional unit represented by the following general formula (1).
[0011] [ka]
[0012] In the formula, Ar represents a tetravalent acid anhydride residue derived from an aromatic tetracarboxylic dianhydride, and R1 represents a divalent diamine residue derived from a diamine compound.
[0013] The metal-clad laminate of the present invention contains 40 or more molar parts of acid anhydride residues derived from a tetracarboxylic dianhydride having a ketone group (-CO-) in the molecule, relative to a total of 100 molar parts of the acid anhydride residues, and contains a total of 50 or more molar parts of diamine residues derived from one or more diamine compounds selected from the group consisting of 4,4'-diaminodiphenyl ether, 4,4'-diaminobenzanilide, and 4,4'-diamino-2'-methoxybenzanilide, relative to a total of 100 molar parts of the diamine residues.
[0014] In the metal-clad laminate of the present invention, the content of the thermally conductive filler in the insulating resin layer may be within the range of 30 to 70 vol %.
[0015] In the metal-clad laminate of the present invention, the insulating resin layer may have a thermal conductivity in a thickness direction of 0.7 W / m·K or more.
[0016] The metal-clad laminate of the present invention may have a tear propagation resistance of 10 mN or more when the insulating resin layer is a resin film.
[0017] In the metal-clad laminate of the present invention, the insulating resin layer may have a thermal expansion coefficient of 30 ppm / K or less when made into a resin film.
[0018] In the metal-clad laminate of the present invention, a peel strength between the insulating resin layer and the metal layer may be 0.8 kN / m or more.
[0019] The method for producing a metal-clad laminate of the present invention is a method for producing the above-mentioned metal-clad laminate. The method for producing a metal-clad laminate of the present invention includes the steps of applying a solution of a polyamic acid containing a thermally conductive filler onto a metal foil and drying the solution to form a first layer coating film; applying a polyamic acid solution not containing a thermally conductive filler onto the first coating film and drying the solution to form a second coating film; a step of heating the coating films of the first and second layers to imidize the polyamic acid and integrate the layers to form an insulating resin layer; Contains: In the method for producing a metal-clad laminate of the present invention, the first layer coating film is formed so that its thickness after curing is within a range of 60% to 95% of the thickness of the insulating resin layer, The second coating film is formed so that its thickness after curing falls within a range of 5% to 40% of the thickness of the insulating resin layer.
[0020] The method for producing a metal-clad laminate of the present invention is a method for producing the above-mentioned metal-clad laminate. The method for producing a metal-clad laminate of the present invention includes the steps of applying a solution of a polyamic acid that does not contain a thermally conductive filler onto a metal foil and drying the solution to form a first layer coating film; applying a polyamic acid solution containing a thermally conductive filler onto the first coating film and drying the applied film to form a second coating film; applying a polyamic acid solution not containing a thermally conductive filler onto the second coating film and drying the solution to form a third coating film; a step of heating the coating films of the first, second and third layers to imidize the polyamic acid and integrate the layers to form an insulating resin layer; Contains: In the method for producing a metal-clad laminate of the present invention, the first layer coating film is formed so that its thickness after curing is within a range of 2% to 20% of the thickness of the insulating resin layer, the second coating film is formed so that its thickness after curing is within a range of 60% to 96% of the thickness of the insulating resin layer; The third coating film is formed so that its thickness after curing falls within a range of 2% to 20% of the thickness of the insulating resin layer. Effect of the Invention
[0021] The metal-clad laminate of the present invention has a metal layer and an insulating resin layer with sufficient mechanical strength for practical use, good adhesion to the metal layer, and excellent thermal conductivity. In addition, the use of thermoplastic polyimide as the matrix resin ensures adhesion to the metal layer, while the incorporation of a thermally conductive filler makes it possible to bring the thermal expansion coefficient close to that of the metal layer, resulting in small warpage and excellent handling characteristics during mass production and processing. Therefore, the metal-clad laminate of the present invention can be widely used industrially as a substrate material for flexible circuit boards, electronic devices, lighting devices, and the like, which require high heat dissipation properties. [Brief description of the drawings]
[0022] [Figure 1] 1 is a diagram showing a manufacturing process of a metal-clad laminate according to one embodiment of the present invention. [Diagram 2] 5 is a diagram showing a manufacturing process of a metal-clad laminate according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] [Metal-clad laminate] A metal-clad laminate according to an embodiment of the present invention includes a metal layer and an insulating resin layer containing a thermally conductive filler. The metal layer is laminated on one or both sides of the insulating resin layer.
[0024] [Insulating resin layer] The insulating resin layer of the metal-clad laminate of the present invention uses a thermoplastic polyimide as a matrix resin and contains a thermally conductive filler in this resin.
[0025] <Polyimide> The thermoplastic polyimide forming the matrix resin of the insulating resin layer is a polyimide containing a constitutional unit represented by the following general formula (1). Here, thermoplastic polyimide is generally a polyimide that can be softened by heating and solidified by cooling, and this process can be repeated. It has a clearly confirmed glass transition temperature (Tg) and a storage modulus of elasticity at 350°C of 1.0×10 8 The storage modulus of a non-thermoplastic polyimide at 350°C is less than 1.0 × 10 Pa. 8 This means polyimide having a modulus of tensile strength of 10 Pa or more.
[0026] [ka]
[0027] In the formula, Ar represents a tetravalent acid anhydride residue derived from an aromatic tetracarboxylic dianhydride, and R1 represents a divalent diamine residue derived from a diamine compound.
[0028] In the above general formula (1), the group R1 represents a diamine residue, and in the present invention, the group R1 essentially contains at least one of the following: a diamine residue (DAPE residue) derived from 4,4'-diaminodiphenyl ether (DAPE), a diamine residue (DABA residue) derived from 4,4'-diaminobenzanilide (DABA), and a diamine residue (MABA residue) derived from 4,4'-diamino-2'-methoxybenzanilide (MABA). DAPE, DABA, and MABA have appropriate flexibility based on their molecular structures, and therefore, in polyamic acid / polyimide using these as the main diamine components (preferably the entire diamine components), it is possible to achieve a nearly balanced balance between thermal expansion and thermal contraction, which is presumed to suppress warping of metal-clad laminates and improve adhesion. The content of at least one of DAPE residues, DABA residues and MABA residues is at least 50 parts by mol in total, preferably at least 80 parts by mol, and more preferably 100 parts by mol, relative to 100 parts by mol in total of diamine residues. If the content of at least one of DAPE residues, DABA residues and MABA residues is less than 50 parts by mol in total, the amount of dimensional change of the insulating resin layer increases during formation of the insulating resin layer (from drying of the coating film of the precursor polyamic acid to the initial stage of curing), and the amount of warping of the intended metal-clad laminate increases.
[0029] In the above general formula (1), the group Ar represents an acid anhydride residue, and therefore, in the present invention, the group Ar essentially contains an acid anhydride residue (hereinafter, sometimes referred to as a "ketone group-containing residue") derived from a tetracarboxylic dianhydride having a ketone group (-CO-) in the molecule. By allowing an abundance of structural units based on the ketone group-containing residue to exist in the polyimide, the adhesion between the insulating resin layer and the metal layer is improved by the interaction between the ketone group in the polyimide and the functional group present on the surface of the adjacently laminated metal layer.
[0030] Examples of tetracarboxylic dianhydrides having a ketone group (-CO-) in the molecule include 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3',3,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 4,4'-(paraphenylene dicarbonyl)diphthalic anhydride, 4,4'-(metaphenylene dicarbonyl)diphthalic anhydride, etc. Among these, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA), 2,3',3,4'-benzophenonetetracarboxylic dianhydride and 2,2',3,3'-benzophenonetetracarboxylic dianhydride are preferred, and BTDA is particularly preferred.
[0031] The functional group having the property of interacting with a ketone group is not particularly limited as long as it can cause, for example, a physical interaction due to intermolecular forces or a chemical interaction due to a covalent bond with the ketone group, and a representative example is an amino group (-NH2). For example, metal foils such as copper foils are surface-treated with a silane coupling agent, and functional groups such as amino groups (-NH2) exist on the surface.
[0032] The content of the ketone group-containing residue is 40 parts by mole or more, preferably 50 parts by mole or more, more preferably 80 parts by mole or more, and even more preferably 100 parts by mole, relative to 100 parts by mole of the total of the acid anhydride residues. If the content of the ketone group-containing residue is less than 40 parts by mole, the effect of improving the adhesion due to the interaction with the functional group of the adjacent metal layer laminated thereon becomes insufficient.
[0033] Among the polyimides represented by the above general formula (1), polyimides having a structural unit in which the group R1 is at least one of a DAPE residue, a DABA residue, and a MABA residue, and the group Ar is a BTDA residue, are most preferred. In other words, by using at least one of DAPE, DABA, and MABA as a diamine compound serving as a raw material for the polyimide in combination with BTDA as an aromatic tetracarboxylic dianhydride, in addition to controlling the thermal expansion coefficient and improving adhesion, the skeleton connecting the aromatic rings is likely to form a planar structure and is likely to be polarized, so that it is likely to be oriented due to intermolecular interactions and to form an ordered structure, and therefore the effect of improving the thermal conduction efficiency is maximized.
[0034] In the general formula (1), examples of diamine compounds which give a diamine residue in which the group R1 is other than a DAPE residue, a DABA residue, or a MABA residue include 4,6-dimethyl-m-phenylenediamine, 2,5-dimethyl-p-phenylenediamine, 2,4-diaminomesitylene, 4,4'-methylenedi-o-toluidine, 4,4'-methylenedi-2,6-xylidine, 4,4'-methylene-2,6-diethylaniline, 2,4-toluenediamine, m-phenylenediamine, p-phenylenediamine, 4,4'-diaminodiphenylpropane, 3,3'-diaminodiphenylpropane, and the like. phenylpropane, 4,4'-diaminodiphenylethane, 3,3'-diaminodiphenylethane, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 3,3-diaminodiphenyl ether, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, benzidine , 3,3'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dimethoxybenzidine, 4,4'-diamino-p-terphenyl, 3,3'-diamino-p-terphenyl, bis(p-aminocyclohexyl)methane, bis(p-β-amino-t-butylphenyl)ether, bis(p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene Examples of suitable diaminophenyl ethers include 2,4-bis(β-amino-t-butyl)toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylylenediamine, p-xylylenediamine, 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, piperazine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,7-diaminodibenzofuran, 1,5-diaminofluorene, dibenzo-p-dioxin-2,7-diamine, and 4,4'-diaminobenzyl.
[0035] Specific examples of aromatic tetracarboxylic dianhydrides that give acid anhydride residues in which the group Ar in the general formula (1) is other than a ketone group-containing residue include pyromellitic dianhydride (PMDA), naphthalene-2,3,6,7-tetracarboxylic dianhydride (NTCDA), naphthalene-1,2,5,6-tetracarboxylic dianhydride, naphthalene-1,2,4,5-tetracarboxylic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride, and naphthalene-1,2,4,5-tetracarboxylic dianhydride. 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-2,3,6,7-tetracarboxylic dianhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride Anhydride, 2,3,6,7-tetrachloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 1,4,5,8-tetrachloronaphthalene-2,3,6,7-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3'',4,4''-p-terphenyltetracarboxylic dianhydride tetracarboxylic dianhydride, 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 2,3,3'',4''-p-terphenyltetracarboxylic dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-propane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3.4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, perylene-2,3,8,9-tetracarboxylic dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, perylene-4,5,10,11-tetracarboxylic dianhydride, perylene-5,6,11,12-tetracarboxylic dianhydride, phenanthrene-1,2,7,8-tetracarboxylic dianhydride, phenanthrene-1, Examples of the dianhydride include 2,6,7-tetracarboxylic dianhydride, phenanthrene-1,2,9,10-tetracarboxylic dianhydride, cyclopentane-1,2,3,4-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, and 4,4'-oxydiphthalic dianhydride.
[0036] When synthesizing the polyimide constituting the insulating resin layer, the diamine and the acid anhydride may each be used alone or in combination of two or more kinds.
[0037] The thermoplastic polyimide constituting the insulating resin layer preferably has a glass transition point (Tg) of 250° C. or higher, and more preferably within the range of 250 to 320° C. If the glass transition point (Tg) is less than 250° C., the heat resistance is poor, and if it exceeds 320° C., there is a risk that sufficient adhesion with the metal layer cannot be ensured.
[0038] <Thermal conductive filler> The content of the thermally conductive filler in the insulating resin layer is preferably within the range of 30 to 70 vol%, and more preferably within the range of 50 to 70 vol%. If the content of the thermally conductive filler is less than 30 vol%, the heat dissipation characteristics when used in electronic components such as circuit boards are insufficient, and if the content exceeds 70 vol%, when the thermally conductive filler is contained in polyimide (polyamic acid), the varnish becomes highly viscous, making it difficult to produce a metal-clad laminate.
[0039] It is important that the particle size of the thermally conductive filler is within the range of 2 μm to 5 μm in terms of uniformly dispersing the filler in the thickness direction of the insulating resin layer to improve thermal conductivity. Here, the "volume average particle size" is the value at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement by the laser diffraction scattering method is 50%. If the volume average particle size of the thermally conductive filler is less than 2 μm, it is difficult to form a thermal conduction path in the thickness direction, and the improvement of thermal conduction efficiency is insufficient. If it is more than 5 μm, the filler protrudes from the surface of the insulating resin layer, causing problems in appearance and surface smoothness, or problems in adhesion with any layer (such as a metal layer) further laminated on the insulating resin layer.
[0040] It is preferable that 80 vol% or more of the entire thermally conductive filler is a spherical filler having a volume average particle diameter in the range of 2 μm to 5 μm. Here, "spherical" means that the shape is spherical or close to spherical, and the ratio of the average major axis to the average minor axis is 1 or close to 1 (preferably 0.8 or more). The spherical filler preferably contains, for example, either one or both of aluminum oxide and aluminum nitride. By using spherical fillers for the majority of the thermally conductive filler, high density filling and uniform dispersion in the insulating resin layer are possible, and the thermal conductivity can be improved. If the content of non-spherical fillers exceeds 20 vol% in total, the appearance is likely to be poor, and voids are likely to occur at the interface between the filler and the resin, which tends to reduce the voltage resistance.
[0041] In the present invention, other thermally conductive fillers can be used together with the thermally conductive filler having a volume average particle size of 2 μm or more and 5 μm or less, as long as the effect of the invention is not impaired. Examples of the thermally conductive fillers other than the above include aluminum, copper, nickel, silica, diamond, magnesia, beryllia, boron nitride, silicon nitride, silicon carbide, etc. Among these, the thermally conductive fillers selected from silica, boron nitride, and silicon nitride are preferred.
[0042] <Structure of insulating resin layer> The insulating resin layer is substantially a single layer. As described later, the formation of the insulating resin layer includes a process of laminating a coating film containing a thermally conductive filler and a coating film not containing a thermally conductive filler by repeatedly applying a polyamic acid solution, which is a precursor of polyimide, multiple times. By repeatedly using the same type of polyamic acid as the polyamic acid used at this time, the multiple layers of coating films are fused and integrated by imidization, and an insulating resin layer is formed in which a single layer of thermoplastic polyimide is the matrix resin. Here, "same type" means that the type of raw material monomer of the polyamic acid is the same. In this way, by forming the insulating resin layer with a single type of thermoplastic polyimide, the thermal conduction efficiency in the thickness direction can be improved. In other words, it is important that the entire matrix resin of the insulating resin layer is composed of a thermoplastic polyimide represented by general formula (1). In this case, in the formation of the multiple layers of coating films, polyamic acids of the same type of raw material monomers and different composition ratios thereof (i.e., the same type of resin) may be used, but in order to improve the heat dissipation efficiency, it is preferable to use the same type (same type) of raw material monomers and the same composition ratios thereof (i.e., the same resin) for all of the multiple layers of coating films.
[0043] The thickness of the insulating resin layer is within a range of 5 μm or more and less than 20 μm, preferably within a range of 8 μm or more and 19 μm or less, and more preferably within a range of 10 μm or more and 18 μm or less. If the thickness of the insulating resin layer is less than 5 μm, the insulating resin layer becomes brittle and easily broken, while if it is 20 μm or more, the thermal resistance becomes high and the heat dissipation efficiency decreases.
[0044] The insulating resin layer preferably has a thermal conductivity in the thickness direction of 0.7 W / m·K or more, more preferably 1.0 W / m·K or more. When the thermal conductivity in the thickness direction of the insulating resin layer is 0.7 W / m·K or more, the heat dissipation characteristics of the metal-clad laminate are excellent, and the metal-clad laminate can be applied to circuit boards and the like used in high-temperature environments. Such excellent thermal conductivity can be achieved by using a polyimide having a structural unit represented by general formula (1) in the insulating resin layer and setting the thickness within the above range. In addition, in the metal-clad laminate of the present invention, the insulating resin layer is particularly formed of a thermoplastic polyimide, so that the adhesiveness with the metal layer can be ensured without the interposition of an adhesive layer, and therefore a high thermal conductivity can be obtained. In this specification, unless otherwise specified, the thermal conductivity means the thermal conductivity (λz) in the thickness direction of the layer.
[0045] The insulating resin layer preferably has a tear propagation resistance (TPR) of 10 mN or more, more preferably 15 mN or more, when the metal layer is removed to leave a polyimide film. If the tear propagation resistance (TPR) is less than 15 mN, it may cause breakage and may impair processability and flexibility. In the present invention, by devising a manufacturing process for a metal-clad laminate as described below, the insulating resin layer can be made thin and good tear propagation resistance can be maintained even if a high concentration of thermally conductive filler is blended therein.
[0046] The insulating resin layer preferably has a thermal expansion coefficient of 30 ppm / K or less, and more preferably in the range of 10 to 25 ppm / K, when the metal layer is removed to leave a polyimide film. When the thermal expansion coefficient is within the above range, warping of the metal-clad laminate can be prevented.
[0047] In the metal-clad laminate of the present invention, the adhesiveness (peel strength) between the insulating resin layer and the metal layer is preferably 0.8 kN / m or more, more preferably 1.0 kN / m or more. In the present invention, in order to obtain a peel strength of 0.8 kN / m or more and to maintain other properties such as reduced warping and heat resistance, 50 mol% or more of tetracarboxylic dianhydride having a ketone group (-CO-) in the molecule is used as the aromatic tetracarboxylic dianhydride, which is the raw material of the polyimide. If the amount of tetracarboxylic dianhydride having a ketone group (-CO-) in the molecule is less than 50 mol% relative to the total acid anhydride components, the peel strength with the metal layer will be less than 0.8 kN / m, and the adhesive strength with the metal layer may be insufficient.
[0048] In addition, the insulating resin layer may contain optional components such as processing aids, antioxidants, light stabilizers, flame retardants, antistatic agents, surfactants, dispersants, anti-settling agents, heat stabilizers, ultraviolet absorbers, and organic or inorganic fillers other than the thermally conductive filler, so long as the optional components do not impair the above-mentioned physical properties.
[0049] [Metal layer] The metal layer in the metal-clad laminate of the present invention is a conductor layer for a heat dissipation substrate or a circuit board, and examples of such metal foils include conductive metal foils such as copper, aluminum, iron, silver, palladium, nickel, chromium, molybdenum, tungsten, zinc, and alloys thereof. Among these, copper foil or an alloy copper foil containing 90% or more of copper is preferably used. The preferred thickness range of the metal layer can be set according to the application of the metal-clad laminate, but when used as a substrate material for electronic devices, lighting equipment, etc., it is preferable to set it within the range of, for example, 5 to 50 μm. If the thickness of the metal layer is less than 5 μm, there is a risk of problems such as wrinkles occurring during transportation in the manufacturing process, and conversely, if it exceeds 50 μm, there is a possibility that the processability is reduced.
[0050] In addition, the conductive metal foil used as the metal layer preferably has a surface roughness (Rz) of 0.05 to 3.5 μm on the surface to be bonded to the insulating resin layer in order to enhance adhesion to the insulating resin layer. If the surface roughness (Rz) of the surface to be bonded to the insulating resin layer is less than 0.05 μm, the metal layer and the insulating resin layer may easily peel off depending on the application of the metal-clad laminate, and for example, the metal-clad laminate is not suitable for use as a flexible substrate material. On the other hand, if the surface roughness (Rz) of the surface to be bonded to the insulating resin layer exceeds 3.5 μm, the adhesion between the metal layer and the insulating resin layer is good due to the anchor effect caused by the roughening, but there is a concern that the wiring shape may deteriorate when the metal layer is processed into wiring.
[0051] [Metal-clad laminate manufacturing method] Next, an example of a method for producing a metal-clad laminate (metal-clad laminate) will be described. A metal-clad laminate can be formed by directly applying a polyamic acid, which is a precursor of polyimide, onto a metal substrate that will become a metal layer, and then drying and curing the polyamic acid. Here, a metal foil such as a copper foil can be used as the metal substrate.
[0052] The filler-containing polyamic acid solution can be applied onto the metal substrate by a known method, for example, a method appropriately selected from bar coating, gravure coating, roll coating, die coating, and the like.
[0053] In order to more clearly explain the present invention, a production example of a metal-clad laminate having a metal layer on one side of an insulating resin layer will be shown with reference to the drawings.
[0054] 1 shows an example of a manufacturing process for a metal-clad laminate 100 according to an embodiment of the present invention. First, a metal foil 10 such as a copper foil that constitutes the metal layer in the metal-clad laminate 100 is prepared. As shown in FIG. 1(a), a polyamic acid solution containing a thermally conductive filler 30 is applied onto this metal foil 10, and then dried at a temperature of 140° C. or less to remove a certain amount of the solvent, thereby forming a coating film 21 of a first layer. Next, as shown in FIG. 1(b), a polyamic acid solution not containing the thermally conductive filler 30 is applied onto the coating film 21, and dried in the same manner as above to form a coating film 23 as a second layer. Next, as shown in FIG. 1(c), the coating films 21 and 23 are heat-treated at high temperature to imidize the polyamic acid, thereby forming a single insulating resin layer 20 in which the coating films 21 and 23 are fused together.
[0055] As shown in FIG. 1, by laminating a coating film 23 not containing a thermally conductive filler 30 on a coating film 21 containing a thermally conductive filler 30 and then performing thermal imidization, the thermally conductive filler 30 does not protrude from the surface of the insulating resin layer 20, and therefore, it is possible to effectively prevent poor appearance and surface smoothness, and a decrease in mechanical strength such as tear propagation resistance, while simultaneously achieving excellent thermal conductivity. In addition, by forming the matrix resin of the insulating resin layer 20 from the same (preferably the same) thermoplastic polyimide, it is not necessary to separately provide an adhesive layer made of a different resin material, and excellent thermal conductivity can be maintained. It is preferable that the thickness of the coating film 23 not containing a thermally conductive filler 30 is as thin as possible as long as the above-mentioned action and effect are exhibited. For example, the first coating film 21 is formed so that its thickness after curing is within the range of 60% to 95% of the total thickness of the insulating resin layer 20, and preferably within the range of 80 to 95%, and the second coating film 23 is formed so that its thickness after curing is within the range of 5% to 40% of the total thickness of the insulating resin layer 20, and preferably within the range of 5 to 20%.
[0056] 2 shows an example of a manufacturing process for a metal-clad laminate 100 according to another embodiment of the present invention. First, a metal foil 10 such as a copper foil that constitutes the metal layer of the metal-clad laminate 100 is prepared. As shown in FIG. 2(a), a polyamic acid solution that does not contain a thermally conductive filler 30 is applied onto this metal foil 10, and then dried at a temperature of 140° C. or less to remove a certain amount of the solvent, thereby forming a first layer coating film 25. Next, as shown in FIG. 2(b), a polyamic acid solution containing thermally conductive filler 30 is applied onto coating film 25, and dried in the same manner as above to form coating film 27 as a second layer. Next, as shown in FIG. 2(c), a polyamic acid solution not containing the thermally conductive filler 30 is applied onto the coating film 27, and dried in the same manner as above to form a coating film 29 as a third layer. Next, as shown in FIG. 2(d), the coating films 25, 27, and 29 are heat-treated at high temperature to imidize the polyamic acid, thereby forming a single insulating resin layer 20 in which the coating films 25, 27, and 29 are fused together.
[0057] As shown in FIG. 2, by laminating a coating film 29 not containing a thermally conductive filler 30 on a coating film 27 containing a thermally conductive filler 30 and then performing thermal imidization, the thermally conductive filler 30 does not protrude from the surface of the insulating resin layer 20, and therefore, it is possible to effectively prevent poor appearance and surface smoothness, and a decrease in mechanical strength, while simultaneously achieving excellent thermal conductivity. In addition, by forming the matrix resin of the insulating resin layer 20 from the same (preferably the same) thermoplastic polyimide, it is not necessary to separately provide an adhesive layer made of a different resin material, and excellent thermal conductivity can be maintained. In addition, by forming a coating film 25 not containing a thermally conductive filler 30 and then forming a coating film 27 containing a thermally conductive filler 30 thereon, it is possible to prevent a decrease in adhesion between the metal foil 10 and the insulating resin layer 20. It is preferable that the thickness of the coating films 25 and 29 not containing a thermally conductive filler 30 is as thin as possible as long as the above-mentioned action and effect are exhibited. For example, the first coating film 25 is formed so that its thickness after curing is within the range of 2% to 20% of the total thickness of the insulating resin layer 20, and preferably within the range of 5 to 15%; the second coating film 27 is formed so that its thickness after curing is within the range of 60% to 96% of the total thickness of the insulating resin layer 20, and preferably within the range of 70 to 90%; and the third coating film 29 is formed so that its thickness after curing is within the range of 2% to 20% of the total thickness of the insulating resin layer 20, and preferably within the range of 5 to 15%.
[0058] Here, the heat treatment for imidization is preferably carried out stepwise for about 15 to 60 minutes at a heating temperature in the range of, for example, 130 to 360°C. Such stepwise heat treatment can reduce dimensional changes in the insulating resin layer 20 at the heat curing stage and suppress warping. If the heat treatment temperature is lower than 130°C, the dehydration ring-closing reaction of polyimide does not proceed sufficiently, and conversely, if it exceeds 360°C, the insulating resin layer 20 and the metal foil 10 may deteriorate due to oxidation or the like.
[0059] The polyamic acid solution containing the thermally conductive filler 30 can be prepared, for example, by adding a predetermined amount of the thermally conductive filler 30 to a polyamic acid solution containing a solvent obtained by polymerization in advance, and dispersing the filler using a stirrer or the like, or by adding a diamine and an acid anhydride while dispersing the thermally conductive filler 30 in a solvent, and polymerizing the filler. Here, the polyamic acid can be produced by a known method in which an aromatic diamine component and an aromatic tetracarboxylic dianhydride component are used in substantially equimolar amounts and polymerized in a solvent. That is, for example, the aromatic diamine component is dissolved in a solvent such as N,N-dimethylacetamide under a nitrogen gas flow, and then the aromatic tetracarboxylic dianhydride is added and reacted at room temperature for about 3 hours to obtain a polyamic acid.
[0060] The preferred degree of polymerization of the polyamic acid suitable for the purpose of forming the insulating resin layer 20 is, when expressed in terms of its viscosity range, preferably in the range of, for example, a solution viscosity of 500 cps to 100,000 cps. If the viscosity is within the above range, the thermally conductive filler 30 can be kept in a uniformly dispersed state even when it is blended. If the viscosity is outside the above range, defects such as uneven thickness and streaks are likely to occur in the film during coating operation using a coater or the like. The solution viscosity can be measured using a cone-plate type viscometer equipped with a thermostatic water bath. Examples of the solvent to be used include N,N-dimethylacetamide, n-methylpyrrolidinone, 2-butanone, diglyme, xylene, etc., and these can be used alone or in combination of two or more kinds.
[0061] In the manner described above, a metal-clad laminate 100 having a structure in which the insulating resin layer 20 is laminated on the metal foil 10 as the metal layer can be manufactured. Furthermore, it is also possible to form a double-sided metal-clad laminate having a laminate structure of metal foil 10 / insulating resin layer 20 / metal layer (not shown) by laminating a metal foil on the insulating resin layer 20 by a method such as thermocompression bonding. When the metal-clad laminate 100 of the present invention is a double-sided metal-clad laminate, the insulating resin layer 20 formed of thermoplastic polyimide not only has excellent adhesion to the metal foil 10 that is the base material on which the coating film is cast, but also has similarly excellent adhesion to the metal layer (not shown) on the laminate side.
[0062] As described above, the metal-clad laminate 100 of the present embodiment employs a manufacturing method including a multiple-application step in which a polyamic acid solution containing a thermally conductive filler 30 is applied and then a polyamic acid solution not containing a thermally conductive filler 30 is applied. As a result, even if the thickness of the insulating resin layer 20 is within a range of 5 μm or more and less than 20 μm, it is possible to obtain a layer having excellent thermal conductivity while avoiding poor appearance and surface smoothness and reduced mechanical strength caused by the incorporation of the thermally conductive filler 30. In addition, since the entire insulating resin layer 20 is formed of thermoplastic polyimide, it has a practical adhesive strength between the metal layer (metal foil 10) and the insulating resin layer 20 without the need for an adhesive layer. In addition, the metal-clad laminate 100 of the present embodiment has small warping and is therefore excellent in handling characteristics during mass production and processing. Therefore, by using it as a circuit board material typified by flexible printed circuit boards (FPCs), the reliability of electronic devices can be improved. Moreover, the metal-clad laminate 100 of the present embodiment can be widely used industrially as a heat dissipation substrate for electronic devices, lighting devices, and the like that require high heat dissipation properties.
[0063] [Circuit board] The circuit board according to one embodiment of the present invention can be manufactured by processing the metal layer of the metal-clad laminate into a pattern by a conventional method to form a metal wiring layer. The patterning of the metal layer can be performed by any method using, for example, photolithography and etching.
[0064] [Polyimide film] The polyimide film according to one embodiment of the present invention is a thermoplastic polyimide film consisting of an insulating resin layer containing a thermally conductive filler, excluding the metal layer of the metal-clad laminate. The polyimide film of this embodiment has the same structure as the insulating resin layer of the metal-clad laminate, and can be produced by removing the metal layer of the metal-clad laminate by etching using a conventional method. Alternatively, in the structure shown in Figures 1 and 2, a peelable substrate is used instead of the metal foil 10, and the process of peeling the substrate after forming the insulating resin layer 20 may be carried out to produce the polyimide film of this embodiment. EXAMPLES
[0065] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the scope of these examples.
[0066] The abbreviations used in the examples represent the following compounds. BTDA: 3,3',4,4'-benzophenonetetracarboxylic dianhydride DAPE: 4,4'-diaminodiphenyl ether DABA: 4,4'-diaminobenzanilide MABA: 4,4'-diamino-2'-methoxybenzanilide PMDA: Pyromellitic dianhydride BAPP: 2,2-bis(4-aminophenoxyphenyl)propane m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl DMAc: N,N-dimethylacetamide
[0067] The properties evaluated in the examples were evaluated according to the following evaluation methods.
[0068] [Viscosity measurement] The viscosity of the polyamic acid solution was measured at 25° C. using a cone-plate viscometer equipped with a thermostatic water bath (manufactured by Tokimec Co., Ltd.).
[0069] [Volume average particle size D 50 Measurement of [Volume average particle size D 50 Measurement of Using a laser diffraction particle size distribution analyzer (manufactured by Malvern Instruments, trade name: Master Sizer 3000), water was used as the dispersion medium and particle size was measured by a laser diffraction / scattering measurement method.
[0070] [Copper foil peel strength] The copper foil layer of the laminate was pattern-etched into a rectangular shape 1.0 mm wide and 180 mm long, and a test specimen 20 mm wide and 200 mm long was cut out so that the pattern was in the center, and a 180° peel test was performed based on IPC-TM-650 (The Institute for Interconnecting and Packaging Electronic Circuits Test Method 650) 2.4.19. ○: 0.8kN / m or more ×: Less than 0.8 kN / m
[0071] [Adhesive peel strength (peel strength)] A fluororesin sheet was placed partially on the polyimide layer of the single-sided metal-clad laminate, and an adhesive sheet (polyimide-based, manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: NB25A-M, thickness: 25 μm) and copper foil 1 (electrolytic copper foil, manufactured by Fukuda Metal Foil & Powder Co., Ltd., product name: CF-T4M-DS-HD-35, thickness: 35 μm, Rz = 1.4 μm) were layered in order, and then the laminate was thermocompressed at 160 ° C for 1 hour at a pressure of 3.5 MPa per unit area to prepare a test piece. The copper foil side of the laminate, which was 5 mm wide and 100 mm long, was fixed to an aluminum plate with double-sided tape, and the adhesive sheet with the copper foil was peeled off in the 180 ° direction at a speed of 50 mm / min starting from the place where the fluororesin sheet was placed, to determine the adhesive peel strength (peel strength). ○: 0.8kN / m or more ×: Less than 0.8 kN / m
[0072] [Thermal conductivity in the thickness direction (λz)] The polyimide resin film was cut into a size of 20 mm × 20 mm, and the thermal diffusivity in the thickness direction was measured by the laser flash method (NETZSCH, product name: Xenon Flash Analyzer LFA447 Nanoflash device), the specific heat was measured by DSC, and the density was measured by the immersion method. The thermal conductivity (W / m K) was calculated based on these results.
[0073] [Measurement of coefficient of thermal expansion (CTE)] A polyimide film (3 mm × 15 mm) was heated from 30°C to 280°C at a heating rate of 10°C / min while applying a load of 5.0 g in a thermomechanical analysis (TMA) device, and then cooled from 250°C to 100°C. The thermal expansion coefficient was measured from the elongation (linear expansion) of the polyimide film as the temperature was lowered.
[0074] [Tear Propagation Resistance (TPR)] A polyimide resin film of 63.5 mm x 50 mm was used as a test piece, a 12.7 mm long cut was made in the test piece, and the tear propagation resistance was measured using a light load tear tester manufactured by Toyo Seiki Co., Ltd. ○: 10mN or more ×: Less than 10mN
[0075] (Synthesis Example 1) Under a nitrogen stream, DAPE (17.31 g, 0.0864 mol) was dissolved in 255 g of DMAc solvent in a 500 ml separable flask with stirring. Then, BTDA (27.69 g, 0.0858 mol) was added. The solution was then stirred at room temperature for 3 hours to carry out a polymerization reaction, yielding a pale yellow viscous polyamic acid solution A.
[0076] (Synthesis Examples 2 to 6) In the same manner as in Synthesis Example 1, the diamines and tetracarboxylic dianhydrides shown in Table 1 were added to carry out a polymerization reaction, to obtain viscous solutions of polyamic acids B to F, which serve as polyimide precursors.
[0077] [Table 1]
[0078] (Combination example 1) 39.6 parts by weight of polyamic acid solution A having a solid content concentration of 15 wt % and aluminum oxide particles [manufactured by Sumitomo Chemical Co., Ltd., product name: AA-3, spherical, volume average particle diameter D 50 3.0 μm] was mixed with 40.4 parts by weight of a thermally conductive filler-containing polyamic acid solution G. The content of aluminum oxide particles in this insulating resin layer was 70 vol %.
[0079] (Combination examples 2~8) As in Formulation Example 1, the polyamic acid solutions and aluminum oxide particles shown in Table 2 were mixed in a centrifugal mixer until homogenous, to obtain polyamic acid solutions H to N containing thermally conductive fillers. In addition, in Blend Examples 3 and 4, aluminum oxide particles [manufactured by Sumitomo Chemical Co., Ltd., product name: AA-2, spherical, volume average particle diameter D 50 2.0 μm] was used.
[0080] [Table 2]
[0081] Example 1 On the copper foil 1, the polyamic acid solution G obtained in Formulation Example 1 was applied so that the thickness after curing was 13 μm, and the solution was dried by heating at 90 to 140 ° C. to remove the solvent. Next, the polyamic acid solution B obtained in Synthesis Example 2 was applied thereon so that the thickness after curing was 1.5 μm, and the solution was dried by heating at 120 ° C. to remove the solvent. After that, the temperature was raised stepwise over 30 minutes in the temperature range of 130 to 360 ° C. to prepare a flexible substrate laminate M1 consisting of two polyimide layers on the copper foil 1. The thickness of the polyimide layer on the copper foil 1 was 13 μm / 1.5 μm in the order of G / B from the copper foil 1 side. In order to evaluate the properties of the polyimide layer in the flexible substrate laminate M1, the copper foil 1 was etched away to prepare a film M1, and the CTE, thickness direction thermal conductivity, and tear propagation resistance (TPR) were evaluated.
[0082] (Examples 2 to 4, 7, and 8, Comparative Examples 2 and 4) By changing the type and thickness of the polyamic acid solution used, laminates for flexible substrates M2 to M4, M7, M8, M10 and M12 and films M2 to M4, M7, M8, M10 and M12 were obtained in the same manner as in Example 1 and evaluated in the same manner.
[0083] Example 5 On the copper foil 1, the polyamic acid solution B obtained in Synthesis Example 2 was applied so that the thickness after curing was 1.0 μm, and the solution was heated and dried at 120 ° C to remove the solvent. The polyamic acid solution I obtained in Formulation Example 3 was applied so that the thickness after curing was 14 μm, and the solution was heated and dried at 90 to 140 ° C to remove the solvent. Next, the polyamic acid solution B obtained in Synthesis Example 2 was applied thereon so that the thickness after curing was 1.0 μm, and the solution was heated and dried at 120 ° C to remove the solvent. After that, the temperature was raised stepwise over 30 minutes in the temperature range of 130 to 360 ° C to produce a flexible substrate laminate M5 consisting of three polyimide layers on the copper foil 1. The thicknesses of the polyimide layers on the copper foil 1 are 1.0 μm / 14 μm / 1.0 μm in the order of B / I / B from the copper foil 1 side. In order to evaluate the properties of the polyimide layer in the laminate M5 for flexible substrates, the copper foil 1 was removed by etching to produce a film M5, and the CTE, thermal conductivity through thickness, and tear propagation resistance (TPR) were evaluated.
[0084] (Example 6, Comparative Example 3) Laminates for flexible substrates M6 and M11 and films M6 and M11 were obtained in the same manner as in Example 5, except that the type and thickness of the polyamic acid solution used were changed, and these were similarly evaluated.
[0085] Comparative Example 1 The polyamic acid solution G obtained in Formulation Example 1 was applied onto copper foil 1 so that the thickness after curing would be 18 μm, and the solution was dried by heating at 90 to 140° C. to remove the solvent. The temperature was then increased stepwise over 30 minutes in the temperature range of 130 to 360° C. to produce a flexible substrate laminate M9 consisting of one polyimide layer on the copper foil 1. In order to evaluate the properties of the polyimide layer in the flexible substrate laminate M9, the copper foil 1 was etched away to produce a film M9, and the CTE, thickness direction thermal conductivity, and tear propagation resistance (TPR) were evaluated.
[0086] The above results are summarized in Tables 3 and 4.
[0087] [Table 3]
[0088] [Table 4]
[0089] From the above results, the metal-clad laminates of Examples 1 to 8 obtained by the manufacturing method including the step of repeating the application of the same type or the same composition polyamic acid solution multiple times and laminating the coating film containing the thermally conductive filler and the coating film not containing the thermally conductive filler in this order were thin films with a thickness of less than 20 μm, and had excellent peel strength on both the copper foil side and the adhesive side, and also had good thickness direction thermal conductivity and tear propagation resistance (TPR). In contrast, Comparative Example 1 using only the coating film containing the thermally conductive filler, Comparative Example 2 in which the order of forming the coating film containing the thermally conductive filler and the coating film not containing the thermally conductive filler is reversed, and Comparative Examples 3 and 4 using resin types different from the present invention did not satisfy all the evaluation items.
[0090] Although the embodiment of the present invention has been described in detail above for the purpose of illustration, the present invention is not limited to the above embodiment, and various modifications are possible. [Explanation of symbols]
[0091] 10...metal foil, 20...insulating resin layer, 21, 23, 25, 27, 29...coating film, 30...thermally conductive filler, 100...metal-clad laminate
Claims
1. A metal-clad laminate comprising a metal layer and an insulating resin layer containing a thermally conductive filler laminated on the metal layer, The thermally conductive filler has a volume average particle size of 2 μm or more and 5 μm or less, The insulating resin layer has a thickness in the range of 5 μm or more and less than 20 μm, and when made into a resin film, has a tear propagation resistance of 10 mN or more, and contains a constitutional unit represented by the following general formula (1): 【Chemistry 1】 [In the formula, Ar represents a tetravalent acid anhydride residue derived from an aromatic tetracarboxylic dianhydride, R 1 means a divalent diamine residue derived from a diamine compound. The matrix resin is a thermoplastic polyimide. A metal-clad laminate comprising: an acid anhydride residue derived from a tetracarboxylic dianhydride having a ketone group (-CO-) in the molecule in a total of 40 molar parts relative to a total of 100 molar parts of the acid anhydride residues; and a diamine residue derived from one or more diamine compounds selected from the group consisting of 4,4'-diaminodiphenyl ether, 4,4'-diaminobenzanilide, and 4,4'-diamino-2'-methoxybenzanilide in a total of 50 molar parts relative to a total of 100 molar parts of the diamine residues.
2. 2. The metal-clad laminate according to claim 1, wherein the content of the thermally conductive filler in the insulating resin layer is within a range of 30 to 70 vol %.
3. 3. The metal-clad laminate according to claim 1, wherein the insulating resin layer has a thermal conductivity of 0.7 W / m·K or more in a thickness direction.
4. The metal-clad laminate according to any one of claims 1 to 3, wherein the insulating resin layer has a thermal expansion coefficient of 30 ppm / K or less when made into a resin film.
5. The metal-clad laminate according to any one of claims 1 to 4, wherein a peel strength between the insulating resin layer and the metal layer is 0.8 kN / m or more.
6. A method for producing a metal-clad laminate according to any one of claims 1 to 5, A step of applying a solution of a polyamic acid containing a thermally conductive filler onto a metal foil and drying the applied solution to form a first layer coating film; applying a polyamic acid solution not containing a thermally conductive filler onto the first coating film and drying the solution to form a second coating film; a step of heating the coating films of the first and second layers to imidize the polyamic acid and integrate the layers to form an insulating resin layer; Including, the first coating film is formed so that its thickness after curing is within a range of 60% to 95% of the thickness of the insulating resin layer; A method for producing a metal-clad laminate, characterized in that the second layer coating film is formed so that its thickness after curing is within the range of 5% to 40% of the thickness of the insulating resin layer.
7. A method for producing a metal-clad laminate according to any one of claims 1 to 5, A step of applying a solution of a polyamic acid containing no thermally conductive filler onto a metal foil and drying the applied solution to form a first layer of a coating film; applying a polyamic acid solution containing a thermally conductive filler onto the first coating film and drying the applied film to form a second coating film; applying a polyamic acid solution not containing a thermally conductive filler onto the second coating film and drying the applied film to form a third coating film; a step of heating the coating films of the first, second and third layers to imidize the polyamic acid and integrate the layers to form an insulating resin layer; Including, the first coating film is formed so that its thickness after curing is within a range of 2% to 20% of the thickness of the insulating resin layer; the second coating film is formed so that its thickness after curing is within a range of 60% to 96% of the thickness of the insulating resin layer; A method for producing a metal-clad laminate, characterized in that the third layer coating film is formed so that its thickness after curing is within a range of 2% to 20% of the thickness of the insulating resin layer.
Citation Information
Patent Citations
Metal-insulating resin substrate and method of manufacturing the same
JP2011177929A
Metal-clad laminate and heat conductive polyimide film
JP2012061793A
Heat conductive polyimide-metal substrate
JP2012213899A
Multilayer resin sheet, resin sheet laminate, cured multilayer resin sheet and method for manufacturing the same, multilayer resin sheet with metal foil, and semiconductor device
JP2013039834A
Resin composition, insulating film, laminated body and method for manufacturing laminated body
JP2014133783A